-6h-14+5h=h+14

Simple and best practice solution for -6h-14+5h=h+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6h-14+5h=h+14 equation:


Simplifying
-6h + -14 + 5h = h + 14

Reorder the terms:
-14 + -6h + 5h = h + 14

Combine like terms: -6h + 5h = -1h
-14 + -1h = h + 14

Reorder the terms:
-14 + -1h = 14 + h

Solving
-14 + -1h = 14 + h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1h' to each side of the equation.
-14 + -1h + -1h = 14 + h + -1h

Combine like terms: -1h + -1h = -2h
-14 + -2h = 14 + h + -1h

Combine like terms: h + -1h = 0
-14 + -2h = 14 + 0
-14 + -2h = 14

Add '14' to each side of the equation.
-14 + 14 + -2h = 14 + 14

Combine like terms: -14 + 14 = 0
0 + -2h = 14 + 14
-2h = 14 + 14

Combine like terms: 14 + 14 = 28
-2h = 28

Divide each side by '-2'.
h = -14

Simplifying
h = -14

See similar equations:

| 6(10+20)=180 | | 16a-10=3a+17 | | x+x-3+x+8+x-5=360 | | 7x-3x=10.2 | | 5x-(3x-6)=22 | | 7x+1=126 | | 6x^3=200 | | 8(2)+n=31 | | 1.4x+13.32=2.35x+21.92 | | (x-9)/7=3x | | 3-4(2x+7)=23 | | 10b-8=12b-10 | | 4(4/2+4)= | | 87+98+90+85=x | | -4(5x+2)=52 | | 8x+4(-4x+7)=34-8x | | x-9/7=3x | | x=43+86+51 | | 13m-21=9m-6 | | 7(2x-3)-3(5x+6)=-4(-3x+5)+5(-4x+5) | | 12-7b=18-9b | | 4x+8y=-44 | | ax+5=bx-cforx | | 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 |

Equations solver categories